2012
DOI: 10.1371/journal.pone.0051123
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Association of Five Candidate Polymorphisms in Apelin/APJ Pathway with Coronary Artery Disease among Chinese Hypertensive Patients

Abstract: BackgroundVia sequencing the genes of apelin/angiotensin receptor-like 1 (apelin/APJ) pathway, we have recently identified and validated four common polymorphisms (rs3761581, rs56204867, rs7119375, and rs10501367) implicated in the development of hypertension. Extending these findings, we, in Chinese hypertensive patients, sought to investigate the association of these four polymorphisms and one additional promising candidate (rs9943582) from this pathway with the risk of developing coronary artery disease (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
4
25
0
3
Order By: Relevance
“…Therefore, the genetic effects might differ when it expressed in different cell types. The sex-specific effect of apelin had been documented in other human studies (Ba et al, 2014;Jin et al, 2012). Similar to ours, a study investigating Chinese obese children showed that the correlation between serum aplein levels and obesity-related biomarkers was only observed in girls, but not in boys (Ba et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the genetic effects might differ when it expressed in different cell types. The sex-specific effect of apelin had been documented in other human studies (Ba et al, 2014;Jin et al, 2012). Similar to ours, a study investigating Chinese obese children showed that the correlation between serum aplein levels and obesity-related biomarkers was only observed in girls, but not in boys (Ba et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…However, the genetic and epigenetic regulations of apelin signaling have not been investigated in HAPE and HA adaptation, even though variants of the genes involved in this signaling have been extensively investigated in several disease conditions (17)(18)(19)(20)(21)(22)(23)(24). Our previous reports on NOS3 revealed a selection of polymorphisms in both HA adaptation and HAPE (17,18).…”
mentioning
confidence: 99%
“…A striking example is provided by one of the first discovered smORFs, apelin. Since its change in annotation from lncRNA to mRNA following its incidental discovery and functional characterization, genomic studies have identified polymorphisms linked to cardiovascular diseases and obesity risks (Zhao et al 2010;Liao et al 2011;Jin et al 2012;Sentinelli et al 2016). Finally, many published studies may need to be re-interpreted in light of the existence of more than one CDS per mRNA, and future overexpression and knockdown experiments will become technically more complex.…”
Section: The Clinical and Research Need For A Better Annotation Systemmentioning
confidence: 99%